The comparison of the frequency and nature of sharps injuries reported by doctors versus nurses from surgical wards in the context of the prevalence of HBV, HCV and HIV: a cross-sectional sero-survey. (1st March 2011) - Ganczak, M; Korzen, M; Ostrowski, M; Starczewski, A; Bohatyrewicz, A; Szych, Z
Abstract : Objective: To evaluate the nature and frequency of sharps injuries among doctors and nurses from the same surgical/gynaecological wards and the prevalence of HIV/HBV/HCV infection, an anonymous cross-sectional sero-survey was conducted in 16 randomly selected hospitals in West Pomerania, Poland, between 01 June, 2009. Results: Response rate: 70.2%, 89 doctors and 414 nurses consented to participate. During the preceding year 50.7% of respondents sustained at least one sharps injury, median number per doctor was 3, per nurse 0. More doctors than nurses were injured (82% vs 44%; p<0.001), 12.3% doctors versus 2.2% nurses (p<0.003) sustained more than 10 injuries. 69.2% of nurses sustained a hollow-bore needle injury versus 8.9% doctors; p<0.001. Rates of recapping: 41.8% doctors versus 43.9% nurses; p>0.84. Underreporting rates: 85% doctors versus 83.5% nurses, p>0.92. In addition, 77.5% of doctors and 84.5% of nurses (p>0.16) never used safe equipment. Infection control training: 68.5% doctors versus 82.1% nurses; p<0.007. Anti-HBc were found in 16.4% (10/89) of doctors and 11.2% (68/414) of nurses, p>0.28; anti-HCV – in 1.1% (1/89) of doctors versus 1.4% (6/414) of nurses, p>0.79; no anti-HIV positive cases were found. Conclusions: Although the prevalence of HBV/HCV infection between doctors and nurses does not differ significantly, some modifiable risk factors for contracting a BBI such as frequency and nature of sharps injuries may differ, which call for tailoring preventive measures to specific job categories. Inadequate training in infection control, recapping, underreporting and lack of safe equipment were additional risk factors for both categories.